-45-12u=-13

Combine u and 12.

-45-u2=-13

Add 45 to both sides of the equation.

-u2=-13+45

To write -13 as a fraction with a common denominator, multiply by 55.

-u2=-13⋅55+45

To write 45 as a fraction with a common denominator, multiply by 33.

-u2=-13⋅55+45⋅33

Write each expression with a common denominator of 15, by multiplying each by an appropriate factor of 1.

Multiply 13 and 55.

-u2=-53⋅5+45⋅33

Multiply 3 by 5.

-u2=-515+45⋅33

Multiply 45 and 33.

-u2=-515+4⋅35⋅3

Multiply 5 by 3.

-u2=-515+4⋅315

-u2=-515+4⋅315

Combine the numerators over the common denominator.

-u2=-5+4⋅315

Simplify the numerator.

Multiply 4 by 3.

-u2=-5+1215

Add -5 and 12.

-u2=715

-u2=715

-u2=715

Multiply both sides of the equation by -2.

-2⋅(-u2)=-2⋅715

Simplify -2⋅(-u2).

Cancel the common factor of 2.

Move the leading negative in -u2 into the numerator.

-2⋅-u2=-2⋅715

Factor 2 out of -2.

2(-1)⋅-u2=-2⋅715

Cancel the common factor.

2⋅-1⋅-u2=-2⋅715

Rewrite the expression.

-1⋅(-u)=-2⋅715

-1⋅(-u)=-2⋅715

Multiply.

Multiply -1 by -1.

1⋅u=-2⋅715

Multiply u by 1.

u=-2⋅715

u=-2⋅715

u=-2⋅715

Simplify -2⋅715.

Multiply -2(715).

Combine -2 and 715.

u=-2⋅715

Multiply -2 by 7.

u=-1415

u=-1415

Move the negative in front of the fraction.

u=-1415

u=-1415

u=-1415

The result can be shown in multiple forms.

Exact Form:

u=-1415

Decimal Form:

u=-0.93‾

Solve for u -4/5-1/2u=-1/3